Working fluid parametric analysis for recuperative supercritical organic Rankine cycles for medium geothermal reservoir temperatures. (March 2020) - Moloney, Francesca; Almatrafi, Eydhah; Goswami, D.Y.
Abstract: The conversion efficiency of geothermal energy is very low. For low-temperature resources, such as geothermal energy, a supercritical organic Rankine cycle (ORC) has been shown to be more efficient than an ORC. Recuperative supercritical ORCs have been proven to yield even higher efficiencies for cases where the heat source is limited above the ambient temperature. Most studies on these cycles have focused on turbine inlet temperatures between 80 and 130 °C. Only a few studies have explored other working fluids between 180 and 350 °C but did not analyze optimum turbine inlet pressures. Turbine inlet temperatures ranging from 170 to 240 °C were tested with the heat source provided by a medium temperature geothermal reservoir. A parametric analysis was performed for various turbine inlet pressures and temperatures. Numerous environmental and nontoxic fluids were analyzed. Temperatures and pressures were selected for each tested fluid to achieve the maximum plant efficiency and net work. The best performing binary cycle fluid was R1233zd(E) with a plant efficiency of 16.2% and a second law efficiency of 52.3% for a turbine inlet temperature of 240 °C. This cycle was compared to a single flash plant. The binary cycle plant produced over double the work and had significantly less exergy destruction. Highlights: A recuperative supercritical ORC was compared to current binary systems. Various environmental and nontoxic fluids were analyzed. Performance of the best performing fluid was compared to a single flash plant. R1233zd(E), butane, isopentane, pentane, and neopentane performed the best.